Action of Ergost-7-en-3- ol from (Acanthaster planci) stimulation of activity peritoneal macrophages - M. Janib Achmad; Ardan Samman; Nebuchadnezzar Akbar (Pensoft Publishers, 2024)
An is a compound capable of influencing the human immune system because it can maintain and restore the balance of the immune system by stimulating the immune system through phagocytosis, the complement system, IgA antibody secretion, the release of interferon α and γ, T and B lymphocytes, specific antibody systems, and cytokines. Immunomodulators can be obtained from natural sources, one of which is Acanthaster planci, which is one of the marine organisms that has important bioactive substances that can act as immunomodulators. The purpose of this research is to determine the immunomodulatory activity of chloroform fractions FrKl3.1.3.1 and FrKl3.1.3.2 and to identify the immunomodulatory compounds from the chloroform fraction FrKl3.1.3.1 of A. planci. The results of the study showed that the macrophage test of the FrKl3.1.3.1 fraction had higher activity compared to FrKl3.1.3.2, while the spectroscopic data analysis results showed that UV-VIS had a maximum absorption at a wavelength (λmax) of 240 nm, FTIR data (cm-1) showed the presence of hydroxyl (-OH) groups, alkene groups (double bonds (C=C)), and aliphatic C-H groups. The 1H-NMR data (CDCl3, 500 MHz) showed six methane groups, ten aliphatic methylene groups (-CH2-), nine geminal methylene groups, one methylene group with a double bond, and 13C-NMR and DEPT 135 data (CDCl3, 125 MHz) indicated that the A. planci FrKl3.1.3.1 fraction had 28 carbon atoms consisting of six methyl (-CH3) carbon atoms, ten methylene (-CH2) carbon atoms, and nine methine (-CH-) carbon atoms. From the spectroscopic analysis data, it is known that the chloroform fraction of A. planci FrKl3.1.3.1 is ergost-7-en-3-ol compound.